1994
DOI: 10.1155/s1064744994000529
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Morbidity After Radical Vulvectomy

Abstract: Objective: This retrospective investigation describes the infectious morbidity of patients following radical vulvectomy with or without inguinal lymph node dissection. Methods: The charts of patients undergoing radical vulvectomy between January 1, 1986, and September 1, 1989, were reviewed for age, weight, cancer type, tumor stage, operative procedure(s), prophylactic antibiotic and its length of use, febrile morbidity, infection site, culture results, significant medical history, and length of use and numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…24 Many factors contribute to the development of perioperative infections in patients with ovarian cancer after cytoreductive surgery, including the microorganism, the environment, and host defense mechanisms, while ovarian cancer patients frequently undergo extensive, prolonged, and highly invasive surgery, experience significant blood loss, have received preoperative chemoradiotherapy, and have primary or secondary hypoimmunity. 17 In the present study, the rate of perioperative infections in patients with ovarian cancer after primary cytoreductive surgery was higher (18.9%) than previously reported, 3,17,18 suggesting the need to take preventive preoperative and perioperative actions to reduce the rate of perioperative infections in these patients in our hospital.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…24 Many factors contribute to the development of perioperative infections in patients with ovarian cancer after cytoreductive surgery, including the microorganism, the environment, and host defense mechanisms, while ovarian cancer patients frequently undergo extensive, prolonged, and highly invasive surgery, experience significant blood loss, have received preoperative chemoradiotherapy, and have primary or secondary hypoimmunity. 17 In the present study, the rate of perioperative infections in patients with ovarian cancer after primary cytoreductive surgery was higher (18.9%) than previously reported, 3,17,18 suggesting the need to take preventive preoperative and perioperative actions to reduce the rate of perioperative infections in these patients in our hospital.…”
Section: Discussioncontrasting
confidence: 58%
“…Perioperative infections were common in women with ovarian cancer after primary cytoreductive surgery in the present study. The urinary tract and surgical wound were the most common infection sites in both groups, 18 but the percentage of urinary tract infections was higher in the second 10-year group (65.0%) compared with the first 10-year group (60.1%). Numerous factors increase the risk of perioperative urinary tract infections during ovarian cancer surgery, including anatomical features, ascending infection from the lower genital tract, invasive instrumentation such as cystoscopy and catheterization, surgical intervention, chemoradiotherapy, and dysbiosis of vaginal microbiota.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Of 225 patients undergoing either radical or modified radical vulvectomy for vulvar cancer at the Mayo Clinic from 1976 to 1990, 4% had a postoperative vulvar infection and 21% had vulvar necrosis. 45 Elg et al 46 reported a 23% wound infection rate associated with radical vulvectomy. The overall rate of wound infection in this database study was low.…”
Section: Discussionmentioning
confidence: 99%